PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP STRUKTUR MODAL DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERATING - Muslichun Muslichun; Supramono Supramono; Indarto Indarto (Universitas Semarang, 2023)
The existence of growth caused by changes in demand, supply, inflation and population growth results in companies needing to pay attention to their capital structure. Capital structure is a problem for companies because it affects company value. To create an optimal capital structure, it is necessary to balance debt with own capital This study aims to analyze the partial effect of liquidity and profitability on capital structure and whether sales growth can moderate liquidity and profitability on the capital structure of Property and Real Estate listed on the Indonesia Stock Exchange for the period 2017–2020. The sample selection technique in this study uses a purposive sampling technique and the results obtained are 35 companies. The results of this study indicate that liquidity is detrimental to capital structure, while profitability does not affect capital structure. Sales growth could not moderate the liquidity and profitability of the capital structure.